THE COHESIVE DEVICES IN HIVER.COM AND ITS IMPLICATION IN TEACHING ONLINE WRITING - Sunjayanto Masykuri, Edi; Sukarni, Semi; Tusino, Tusino; Dewi, Puspa (Jurnal Ilmu Bahasa, Sastra dan Pengajarannya, 2022)
This research belongs to descriptive qualitative research. The aim of this research to find out the types of cohesive devices in job advertisements and to describe the application the analysis of cohesive devices in job advertisements for teaching writing. The researcher took three job advertisements in hiverhq.com accessed on 16 December 2021. The researcher analyzed the grammatical cohesion and lexical cohesion in sentence based on theory from M.A.K Haliday and Ruqaiya Hasan. The result of this research showed that there were 6 references and 34 conjunctions for grammatical cohesions and 20 repetitions and 3 superordinates for lexical cohesion. However, in grammatical cohesions there was no substitution and ellipsis, whereas in lexical cohesion there is no synonymy or near-synonymy, general word and collocation.